SISTEM INFORMASI APLIKASI LAYANAN PELANGGAN PADA PT. PLN (PERSERO) AREA PONTIANAK BERBASIS SMS GATEWAY - Sabarudin . (Faculty of Engineering, Universitas Tanjungpura, 2014)
Access to information and technological developments bring changes in various systems in line with human life. One of the sample is the system of business services to the public service even PT . PLN ( Persero ) Pontianak district, where the using of information systems becomes very important in the implementation of services to customers. To provide accurate and accountable, to use one of the reliable communication services and low cost is a short message or Short Message Service ( SMS ) that provided by mobile phone operators. A service will be integrated with Information Systems and can provide information such as customer data and the amount of the bill. In addition the system also provides a complaints service that customers can use who experience obstacles in the field. These features will be supported with existing resources so it can produce an interactive system. Application Information System Customer Service at PT.PLN (Persero) Pontianak district, SMS Gateway Based provides interactive information systems services directly to customers in order to improve the quality care that is affordable and flexible, especially for the customers of PT . PLN ( Persero ) Pontianak district that has cell phone and registered in the database. Keywords: Information Systems, Short Message Service, SMS Gateway, Database.// //